Risk Perception as Mediator in the Effect of Financial Literacy to Entrepreneurial Orientation among MSMEs - Tiara Carina; Ni Made Indah Mentari; I Dewa Made Arik Permana Putra; Melani Gita Sari; Ni Putu Tasiya Purnama Dewi (Faculty of Economics and Business Udayana University, 2023)
This study aims to analyze the mediating role of risk perception on the effect of financial literacy to entrepreneurial orientation. From a total population of 32,026 MSMEs in Denpasar, 244 samples were taken through purposive sampling. Data were collected through the administration of Financial Literacy Instruments (rxx=0.639-0.891; r=0.974), Risk Perception Instruments (rxx=0.873-0.956; r=0.989), and Entrepreneurship Orientation Instruments (rxx=0.894-0.988; r=0.988). According to data analysis with Partial Least Square (PLS), it was found that financial literacy significantly affects entrepreneurial orientation; financial literacy significantly influences risk perception; risk perception significantly influences entrepreneurial orientation; and risk perception partially mediates the effect of financial literacy to entrepreneurial orientation in MSMEs in Denpasar. It was found that 49.8% of the variation in the entrepreneurial orientation variable is explained by financial literacy and risk perception variables, while the remaining 50.2% is contribution of other variables outside this research. Keyword: risk perception, financial literacy, entrepreneurship orientation, MSME